QoS INVESTIGATION ON MOODLE’S VIDEO CONFERENCE - LINAWATI, LINAWATI (Jurnal Teknologi Elektro; Vol 10 No 1 (2011): VOL 10, NO 1 (2011): JURNAL TEKNOLOGI ELEKTRO, 2013)
Learning Management System (LMS) supports e-learning as a distant learning. Moodle is one of open source LMS applications that allow embedding multimedia into learning activity in a course, such as video conference session. The paper investigates quality of service (QoS) of video conference session embedded in Moodle, i.e. end-to-end delay, jitter, throughput, packet loss and PSNR. Three scenarios were implemented in the experiment. The scenarios were applied on both wire and wireless transmission, and p2p and p2m connections. The investigation results show that the QoS of video conference session meets the standards issued by ITU-T G.1010 and G.114, for minimum bandwidth of 128 kbps. Thus the application of video conferencing that is integrated in Moodle can run well with minimum bandwidth of 128 Kbps.
Keywords: Video conference, Moodle, QoS